2022
DOI: 10.1002/adbi.202101184
|View full text |Cite
|
Sign up to set email alerts
|

Small‐Molecule‐Driven Direct Reprogramming of Fibroblasts into Functional Sertoli‐Like Cells as a Model for Male Reproductive Toxicology

Abstract: Sertoli cells (SCs) are vital to providing morphological and nutritional support for spermatogenesis. Defects in SCs often lead to infertility. SCs transplantation is a promising potential strategy to compensate for SC dysfunction. However, isolation of SCs from testes is impractical due to obvious and ethical limitations. Here, a molecular cocktail is identified comprising of pan‐BET family inhibitor (I‐BET151), retinoic acid, and riluzole that enables the efficient conversion of fibroblasts into functional S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…In our previous study, we accidentally found that riluzole, the first drug approved by the FDA for the clinical treatment of amyotrophic lateral sclerosis (ALS), had the ability to induce reprogramming of mouse embryonic fibroblastic cells (MEFs) into Sertoli-like cells (CiSCs) (Y. Yang, Li, et al, 2022). Interestingly, our study also revealed that treatment with riluzole resulted in a significant upregulation of gene expression levels of various secreted factors in SCs.…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations
“…In our previous study, we accidentally found that riluzole, the first drug approved by the FDA for the clinical treatment of amyotrophic lateral sclerosis (ALS), had the ability to induce reprogramming of mouse embryonic fibroblastic cells (MEFs) into Sertoli-like cells (CiSCs) (Y. Yang, Li, et al, 2022). Interestingly, our study also revealed that treatment with riluzole resulted in a significant upregulation of gene expression levels of various secreted factors in SCs.…”
Section: Introductionmentioning
confidence: 76%
“…In our previous study, we found that riluzole had the ability to induce the transformation of mouse embryonic fibroblasts into Sertoli-like cells (Y. Yang, Li, et al, 2022). These Sertoli-like cells showed increased expression of key cytokines (Gdnf, Bmp4, Scf, Cxcl12, Inhibin B, and Fgf2) involved in the regulation of spermatogonial stem cell proliferation and differentiation.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Interestingly, SCs are essential for maintaining the structure and function of spermatogenic cell. SCs are adjacent to the spermatogenesis cells and are vital to providing morphological and nutritional support for spermatogenesis, it have been widely studied in recent years [4]. In addition, SCs participate in the formation of the BTB (made of tight, adherens and gap-junctions between SCs) [5], and the primary function of the BTB is to restrict the paracellular ow of water and nutrients across the SCs epithelia and at the same time to protect the developing haploid forms of male germ cells by establishing an immune-privileged environment [6].…”
Section: Introductionmentioning
confidence: 99%